Perception of the World through the Prism of Culture - Harutyunyan, Narine (Armenian Folia Anglistika, 2013)
The world is not perceived as static. It is in constant movement and is described by religious beliefs, cultural traditions, moral values and a system of stereotypes. While perceiving the world man creates cognitive patterns which, together with individual meanings, reflect common underlying features of the world perception among different people. Among the standards that might describe and characterize the world are: visual images, smells and scents, i.e. perceptions received through different senses.